Environmental drivers, spatiotemporal dynamics, and pollination effectiveness of insect floral visitors in Australian seed carrot agroecosystems - Davis, Abby E.; Schmidt, Lena A.; Santos, Karen C.B.S.; Rowbottom, Raylea; Lucas, Amy; Harrington, Samantha; Spurr, Cameron; Rader, Romina (Agriculture, ecosystems & environment, 2025)
Hybrid cropping systems generally depend on insect pollinators to produce high quality yields. In this study, we identified the floral insect community of Australian carrot agroecosystems and evaluated how the location of plants within fields and select environmental conditions (temperature, relative humidity) impacted visitor abundance to carrot flowers. We further evaluated the pollination effectiveness of select insect visitors based on the time of day the pollination event took place. Out of 26,083 carrot floral visitors observed, we identified 52 different insects (33 species and 19 morphospecies) from 26 families. Of these visitors, 86 % belonged to the families Coccinellidae (Coleoptera), Apidae (Hymenoptera), Halictidae (Hymenoptera), and Syrphidae (Diptera). Wild variegated lady beetles (Hippodamia variegata Goeze, 1777) were the most abundant floral visitor observed on hybrid parent lines, while European honey bees (Apis mellifera Linnaeus, 1758) were the most abundant visitor of open-pollinated lines. The abundance of common bee, beetle, and fly taxa differed throughout the day (range: 05:00–17:00) based on temperature (10.5ºC to 39.5ºC) and relative humidity (19.7 %–94.7 %). Further, temporal complementary was observed in measures of pollination performance as A. mellifera and the European drone fly, Eristalis tenax (Linnaeus, 1758), deposited more pollen grains onto hybrid carrot floral stigmas compared to the native halictid bee Lasioglossum cognatum (Smith, 1853) before 12:00 (05:00–12:00), while L. cognatum deposited more pollen grains onto flowers compared to A. mellifera and E. tenax after 12:00 (12:00 and 17:00). The results of this study imply that integrated management practices to support the resource needs of wild bee and fly taxa can potentially provide increased pollination services to carrot seed crops. •Lady beetles, honey bees, halictid bees, and syrphid flies were the dominant floral visitors of Australian seed carrot crops.•Bee and lady beetle abundance varied by plant line, temperature, and humidity, while fly abundance remained consistent.•Honey bees were more abundant in field centers, while halictid bees and some lady beetles were more abundant along field edges.•Honey bees, halictid bees, and Eristalis tenax L. successfully deposited pollen, but effectiveness varied by time of day.